CONTRIBUTION OF UNN RADIOPHYSICISTS TO DEFENSE, SCIENCE, AND INNOVATION - Sergey N. Gurbatov; Valeriy V. Matrosov; Arkadiy V. Yakimov (Высшее образование в России)
The article gives a brief information about the history of the UNN Radiophysics Faculty, about the system of education and scientific achievements of the Faculty and its ties with Russian and international research centers. Radiophysics Faculty was established in 1945 and it became the first faculty in the Soviet Union to prepare specialists in radiophysics for scientific research centres and laboratories of radiolocation and electrovacuum industry. "Students should get scientific knowledge at first hand" and "Teach to learn" are the main pedagogical postulates of the teaching staff. Fundamental physical and mathematical education and an individual approach are the foundations of learning process organization at the Faculty. There are two research schools for master's degree and postgraduate students at the Faculty: "Vibration and wave processes in natural and artificial media" and "Laser physics". Thus, the education process is closely connected with academic research.